Respostas
respondido por:
0
Resposta:
Explicação passo a passo:
Anexos:
alexandremacedo8080:
O 3 passa negativo para o segundo membro
respondido por:
0
Resposta:
S = {(x, y)} = {(3, 9)}
Explicação passo a passo:
.
x+ y = 12
x - y = - 6 .... (soma as duas)
.
==> 2x = 6
........x = 6 : 2
........x = 3
.
x + y = 12
y = 12 - x
y = 12 - 3
y = 9
.
(Espero ter colaborado)
S = {(x, y)} = {(3, 9)}
Explicação passo a passo:
.
x+ y = 12
x - y = - 6 .... (soma as duas)
.
==> 2x = 6
........x = 6 : 2
........x = 3
.
x + y = 12
y = 12 - x
y = 12 - 3
y = 9
.
(Espero ter colaborado)
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás